Analisis Beban Kerja Karyawan di Restoran Ayam Geprek Sambel Cenghar Menggunakan Metode NASA-TLX - Nurul Dwi Astuti; Daisy Ade Riany Diem; Imas Widowati (Sekolah Tinggi Teknologi Wastukancana, 2025)
Workload is a critical factor influencing employee performance and well-being, particularly in fast-paced work environments such as fast-food restaurants. Employee complaints and differing perceptions regarding the most demanding aspects of the job indicate a potential workload imbalance. This study aims to analyze employee workload levels, identify the most influential NASA-TLX dimensions, and explore factors contributing to high workload at Ayam Geprek Sambel Cenghar Restaurant. The research method used the NASA-TLX (Task Load Index), which measures workload based on six dimensions: mental demands, physical demands, temporal demands, performance, effort, and frustration levels. Data were obtained from 21 respondents from four operational departments: cashiers, kitchen staff, waitstaff, and chili sauce mashers (grinding). The results showed that 48% of employees were in the medium workload category, 38% in the high category, and the remainder in the low category. The dimensions with the highest scores and contributing the most to the overall workload were physical demands and effort, each contributing 18%. Based on respondents' responses, it was found that long work hours (12 hours) were the main factor increasing workload. Therefore, an evaluation of work hours, including the implementation of a rotating work system (shift), was recommended to reduce fatigue and improve operational efficiency.